Investigation into obedience in the face of unethical behavior - Salama, Nadiatus; El-Rahman, Medina Janneta; Sholihin, Mahfud (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
Significant concern about obedience in the face of unethical behavior in many corporate scandals is growing worldwide. However, the issue is underexplored because this type of research is faced by the challenge that the perpetrators are reluctant to harm their image by admitting their wrongdoings. The purpose of this study is to obtain a deeper understanding of the human aspects of obedience in the face of unethical behavior among employees in organizations. Using a qualitative cross-case approach, ten employees were interviewed, representing top, middle, and low-level employees in a broad range of private medium-to-large-sized enterprises. The analysis process involved reducing the raw data into meaningful themes, particularly why employees perform unethical behavior. The study's findings provide complex reasons for obedience in the face of unethical behavior, and it is shown to be the rule and habit of organizations. The respondents also explained why they justified their misbehavior. The employees' viewpoints on obedience in the face of unethical behavior will be useful for organizations to curb unlawful practices in the workplace, as these have detrimental effects on them.